Morphological tuning of photo-booster g-C3N4 with higher surface area and better charge transfers for enhanced power conversion efficiency of quantum dot sensitized solar cells. (September 2017) - Ansari, Mohammad Shaad; Banik, Avishek; Qureshi, Mohammad
Abstract: Photo-booster effect of g-C3 N4 Nanotubes (g-C3 N4 NTs) on the photovoltaic properties are investigated using the composites having ZnO Nanorods (ZnO NRs) with different composition ratios, sensitized by CdS quantum dots. Enhanced performance is attributed to the cumulative effects of this composite i.e., (i) a significant decrement of fluorescence intensity in steady state PL, (ii) faster electron lifetime and good electron injection rate from dynamic PL, and (iii) sufficient loading of sensitizer at photoanodic scaffold for better harvesting of solar energy. An increase of 32% in power conversion efficiency (PCE, η) is observed in case of g-C3 N4 NTs based device as compare to g-C3 N4 Nanoflakes (g-C3 N4 NFs). Increased PCE value is mainly due to (i) efficient separation and transportation of the photogenerated charge carriers along a one dimensional (1D) path, resulting in shorter lifetime of charge carriers and (ii) high surface area which provides more active sites for loading of sensitizer particles, results in an improvement of light harvesting ability. Further, electrochemical impedance spectroscopic (EIS) analyses showed an efficient interfacial charge transfer by reducing the recombination processes i.e., the back transferring of photoexcited electron at electrode/electrolyte interface. Graphical abstract: